Community Service-Based Accounting Education for Financial Awareness Development in the United States - Yitian Zhang (CV Edujavare Publishing, 2024)
The rapid development of global economic systems and digital financial technology has increased the importance of accounting literacy and financial awareness in modern society. Accounting education is considered an essential strategy for improving financial management skills, economic responsibility, and sustainable community development. This community service program aims to strengthen financial awareness through community service-based accounting education in the United States. The program employed a qualitative participatory approach involving students, workers, small business owners, and community members through workshops, mentoring activities, accounting simulations, and collaborative learning sessions. Participants were introduced to budgeting techniques, bookkeeping principles, financial reporting systems, digital accounting technologies, and ethical financial management practices to improve accounting competence and responsible financial behavior. The results demonstrated that participants experienced significant improvement in accounting literacy, budgeting competence, financial recording abilities, and confidence in managing financial information systematically. In addition, collaborative educational activities encouraged active participation, problem-solving skills, and awareness regarding financial transparency and accountability. Despite challenges related to technological access, educational diversity, and varying levels of accounting understanding, continuous mentoring and participatory educational approaches contributed positively to the implementation process. Overall, community service-based accounting education provided valuable opportunities for improving financial awareness, strengthening economic resilience, and supporting sustainable community development in the United States. The educational approaches implemented in this program can also serve as important references for developing accounting literacy and financial empowerment programs in other educational and social contexts worldwide.